Design of cable pipeline fault location device based on dynamic laser scanning. Issue 1 (1st November 2022) - Li, Zhongxing; Zhang, Caihong; Huang, Guojian; Ma, Haixia
Abstract: Aiming at the problem that some of the spare power cable pipelines without cable are damaged, and there is no effective detection equipment to detect the blocked state of the pipeline. This paper proposed a dynamic laser scanning method for obstacles in the pipeline, and designed a power pipeline fault positioning device. The infrared laser ranging technology based on time-of-flight is used to dynamically detect the distance between obstacles in the pipeline and the laser sensor, so as to detect the status and location of pipeline blockage. Taking ARM microcontroller as the core, equipped with VL53L0X laser module, the hardware design of the device was completed, and the software program was completed based on the Keil μVision5 IDE environment. The measurement and error analysis of obstacles of two different materials are carried out. The results show that the longer the measurement distance, the larger the error, and the highest measurement error is 1.47%, which fully meets the needs of engineering measurement.